Low fertility in Europe : is there still reason to worry? - Hoorens, Stijn (RAND Corp., 2011)
Recent statistics suggest that fertility in Europe shows signs of recovery after decades of year-on-year drops. This report updates a study on low fertility from 2004 and explores the extent, causes and consequences of the recent recovery.